A Regional Scale Evaluation of Conservation Status of Orchid Species Recorded in The Eastern Mediterranean Region of Turkey - Gülden Sandal Erzurumlu; Kemal Tuluhan Yılmaz; Zerrin Söğüt (Turkish Journal of Agriculture: Food Science and Technology)
In this study, the threat categories of locally endangered orchid species were sampled over an area of covering 187 km2 in Mersin, Adana, Hatay and Kahramanmaraş provinces of Turkey. Periodic observations were carried out in 44 sampling plots specified within three bioclimatic belts, namely the Mediterranean-montane, the sub-Mediterranean and the Mediterranean. 34 orchid species were identified under the genera of Cephalanthera (L.), Comperia (Steven.), Dactylorhiza, Epipactis (L.), Himantaglossum (Boiss.), Limodorum (L.) Ophrys, Orchisand Serapias (Burm.fil). The results revealed that six orchid species were growing in the Mediterranean-montane zone, 20 species in the sub-Mediterranean zone and 23 species in the Mediterranean zone. According to the resources of the International Union for Conservation of Nature (IUCN) the threat categories were reported for only 12 out of 13 species. Local threat categories of this study showed some differences when IUCN data were considered. 34 orchid species identified in this study and 12 species were evaluated under Critically Endangered (CR) threat category. It was found that 11, 7, 2 and 2 species were under EN, VU, NT and LC respectively. Therefore, Orchid species sampled from the Eastern Mediterranean Region of Turkey have been categorized on the basis of the threat categories identified by the IUCN.